2021
DOI: 10.1007/s11259-021-09816-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and codon usage analysis for replicase and capsid genes of porcine circovirus 3

Abstract: Porcine circovirus type 3 (PCV3) is a highly contagious virus belonging to the family Circoviridae that causes the severe dermatitis and nephropathy syndrome. To date, PCV3 has a worldwide distribution and bring huge economic loss in swine industry. Replicase protein (Rep) and capsid protein (Cap) are two major proteins of PCV3. Considering that the large number of new PCV3 isolates were reported in the past few years and the research for the codon usage pattern of Rep and Cap genes was still a gap, phylogenet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
4
4
0
Order By: Relevance
“…Such a finding would imply that composition constraints played an important role in PCV codon usage bias. The results were consistent with the previous studies on PCV-2 [32] and PCV-3 [33], respectively. Furthermore, the frequencies of A3, U3, G3, C3 were very different from the overall frequencies of A, U, G, C regardless of the PCV species studied, which indicated that selection pressure may play a role during the formation of PCV codon usage pattern.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Such a finding would imply that composition constraints played an important role in PCV codon usage bias. The results were consistent with the previous studies on PCV-2 [32] and PCV-3 [33], respectively. Furthermore, the frequencies of A3, U3, G3, C3 were very different from the overall frequencies of A, U, G, C regardless of the PCV species studied, which indicated that selection pressure may play a role during the formation of PCV codon usage pattern.…”
Section: Discussionsupporting
confidence: 93%
“…The ENC values for all PCV species fluctuated around 54.7 ± 0.871, indicating a low bias in these viruses, which may improve the replication of PCVs in their host by reducing the competition during translation. Additionally, the ENC-plot suggested that besides mutation pressure, other factors also affected the codon usage pattern of PCVs, which was consistent with previous reports [31][32][33]. The imbalanced frequency of A3, U3 and G3, C3 in PCVs indicated by PR plot suggested a relevant role of natural selection in shaping the codon usage pattern of the viruses.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, the codon bias is always influenced by external factors to varying degrees. Natural selection has been shown to play a major role in PCV-2 and canine circovirus [50,51], but mutation is more important in duck circovirus codon bias [52]. Although these viruses are closely related, different factors have influenced their evolution.…”
Section: Discussionmentioning
confidence: 99%